The Obligation of Notary to Prevent and Eradicate Criminal Acts of Money Laundering - Dian Ramadhani (International Journal of Multicultural and Multireligious Understanding, 2020)
Notary as general official and as a trusted person because his office has an obligation that is one of which is stipulated in article 16 paragraph (1) Letter F. The Law of Tenure Notary (hereinafter referred to UUJN) namely to keep the contents of the deed and all the information obtained in the making of the deed unless the law determines otherwise. However, in government Regulation No. 43 of 2015 on reporting Parties in the prevention and eradication of Money laundering crimes, notary Public is given the obligation to report to The Financial Transaction Reporting and Analysis Center (hereinafter referred to PPATK) regarding suspicious financial transactions conducted by its clients. So there is a conflict of norms on both provisions. This research aims to assess and analyse the arrangements and responsibilities and responsibilities of notary public in the prevention and eradication of money laundering crimes. This method of research uses normative research methods. The approach which is used in this study are the statutory approach and conceptual approach. The results of this research are regulatory obligations of notary in the prevention and eradication of Money laundering crimes against the secret obligation of the position that these two obligations are not contradicted. The notary is obliged to report to the PPATK, if the notary acts for interest or for and on behalf of the service user. If a notary is acting in accordance with the Authority as stipulated in the UUJN, the notary is not obliged to report any suspicious financial transactions made by his clients. Secondly, the obligation and responsibility of the notary in the prevention and eradication of Money Laundering Crimes is legally notarized liable for alleged criminal acts of money laundering when it acts for the benefit of or for behalf of the service user to objects that are required to be reported, by applying the principle of recognizing the service users, the principle of recognizing the benefit owners of corporations and delivering suspicious financial transaction.